A lepidopteran-specific gene family encoding valine-rich midgut proteins - Odman-Naresh, Jothini; Duevel, Margret; Muthukrishnan, Subbaratnam; Merzendorfer, Hans (My University, 2014)
Many lepidopteran larvae are serious agricultural pests due to their feeding activity. Digestion of the plant diet occurs mainly in the midgut and is facilitated by the peritrophic matrix (PM), an extracellular sac-like structure, which lines the midgut epithelium and creates different digestive compartments. The PM is attracting increasing attention to control lepidopteran pests by interfering with this vital function. To identify novel PM components and thus potential targets for insecticides, we performed an immunoscreening with anti-PM antibodies using an expression library representing the larval midgut transcriptome of the tobacco hornworm, Manduca sexta. We identified three cDNAs encoding valine-rich midgut proteins of M. sexta (MsVmps), which appear to be loosely associated with the PM. They are members of a lepidopteran-specific family of nine VMP genes, which are exclusively expressed in larval stages in M. sexta. Most of the MsVMP transcripts are detected in the posterior midgut, with the highest levels observed for MsVMP1. To obtain further insight into Vmp function, we expressed MsVMP1 in insect cells and purified the recombinant protein. Lectin staining and glycosidase treatment indicated that MsVmp1 is highly O-glycosylated. In line with results from qPCR, immunoblots revealed that MsVmp1 amounts are highest in feeding larvae, while MsVmp1 is undetectable in starving and molting larvae. Finally using immunocytochemistry, we demonstrated that MsVmp1 localizes to the cytosol of columnar cells, which secrete MsVmp1 into the ectoperitrophic space in feeding larvae. In starving and molting larvae, MsVmp1 is found in the gut lumen, suggesting that the PM has increased its permeability. The present study demonstrates that lepidopteran species including many agricultural pests have evolved a set of unique proteins that are not found in any other taxon and thus may reflect an important adaptation in the highly specialized lepidopteran digestive tract facing particular immune challenges.
Citation: Odman-Naresh J, Duevel M, Muthukrishnan S, Merzendorfer H (2013) A Lepidopteran-Specific Gene Family Encoding Valine-Rich Midgut Proteins . PLOS ONE 8(11): e82015. https://doi.org/10.1371/journal.pone.0082015
Keywords: Lepidopteran insects; Agricultural pests; Peritrophic matrix; Midgut